Homologous recombination-dependent repair of telomeric DSBs in proliferating human cells - Pingsu Mao (Nature Portfolio, 2016)
Telomeres protect the ends of chromosomes from the DNA damage recognition machinery, however how damage in telomeres is repaired is poorly understood. Here the authors use CRISPR-Cas9 to induce DNA breaks and identify proliferation dependent homologous recombination repair.